Misogynistic language in song lyrics by Black and Caucasian lyricists / Nurfaqihah Maisarah Mohd Rashidi … [et al.] - Mohd Rashidi, Nurfaqihah Maisarah; C Suppiah, Puspalata; Selvanayagam, Sivajothy; Mylvaganam, Gopighantan (Universiti Teknologi MARA, 2023)
Misogyny permeates every aspect of daily life, including cultural traditions, beliefs, spoken words, and, in the case of this study, contemporary songs. Feminist theories claim that men oppress and objectify women through patriarchal language. This research aims to identify the uses of misogynistic language in song lyrics by Black and Caucasian lyricists using qualitative content analysis. A total of 10 songs were selected for analysis. The results of the content analysis revealed two major types of misogynistic language in song lyrics: blaming and name-calling. It was found that Caucasian lyricists use a more implicit or covert means of expressing misogyny, whereas Black lyricists are more explicit or overt. Finally, this research seeks to educate and raise readers' awareness about the use of misogyny language, specifically in contemporary songs and its relationship to social practices.